19-element vertical cavity surface emitting laser arrays with inter-vertical cavity surface emitting laser ridge connectors. (1st October 2020) - Haghighi, Nasibeh; Moser, Philip; Zorn, Martin; Lott, James A
Abstract: We achieve record concurrent combinations of bandwidth (18 GHz), optical output power (150 mW), and wall plug efficiency (30%) with a unique arrangement of 19-element, electrically parallel 980 nm vertical cavity surface emitting laser (VCSEL) arrays. We use a new two-dimensional, quasi honeycomb geometry with inter-VCSEL ridge connectors—made nonconducting by selective thermal oxidation—to improve heat dissipation and facilitate a single top surface anode contact. Via on-wafer probing we perform static and dynamic measurements over the wide temperature range of 23 °C to 85 °C and extract, report, and discuss key array figures-of-merit.